Synergistic impact of plasma albumin and cognitive function on all-cause mortality in Chinese older adults: a prospective cohort study - Li, Zhi-qiang; Liu, Xin-xin; Wang, Xue-feng; Shen, Chen; Cao, Feng; Guan, Xin-miao; Zhang, Ying; Liu, Jian-ping (Frontiers in Nutrition, 2024)
Background: Hypoalbuminemia and cognitive impairment (CI) each independently increase the mortality risk in older adults. However, these two geriatric syndromes can occur simultaneously. In community-dwelling older adults, is the combination of hypoalbuminemia and CI linked to a higher mortality risk than either condition alone? Objective: We aimed to investigate the association between plasma albumin, cognitive function, and their synergistic effect on mortality in Chinese community-dwelling older adults. Methods: Data from the Chinese Longitudinal Healthy Longevity Survey (2012) included 1,858 participants aged ≥65. Baseline assessments comprised albumin levels and cognitive status. All-cause mortality was confirmed through 2014-2018 surveys. Cox proportional hazards models assessed associations, and restricted cubic splines explored albumin-mortality relationship. Results: During a median follow-up of 48.85 months, 921 deaths occurred. Albumin≥35g/L vs <35g/L[HR : 1.33 (95% CI, 1.10, 1.62)] and CI vs normal cognition [HR : 1.69 (95% CI, 1.43, 1.99)] independently predicted mortality. A dose-response relationship with mortality was observed for albumin quartiles (P < 0.001). Each SD increase in MMSE or albumin correlated with 22% and 15% lower mortality risk, respectively. Combined hypoproteinemia and cognitive impairment (CI) increased the mortality risk by 55%, with a notably higher risk in males, those aged <85 years, and individuals living in rural areas. Interaction effects of albumin and CI on mortality were observed (P <0.001). Mortality risk increased by 61% in the hypoproteinemia group with CI, compared to the normal albumin group. Restricted cubic spline revealed a reverse J-shaped association, particularly for participants without CI. For individuals with CI, albumin levels were inversely associated with mortality risk. Conclusion: Hypoproteinemia and CI, individually and combined, increased all-cause mortality risk in Chinese older adults, with stronger effects in males and younger older adults. These findings emphasize the importance of targeted adjustments and early nutrition programs in health prevention and clinical care for older adults.